Aesthetics of the rhetorical composition in Gibran's texts - ناصر, بشير; سليمان, بثينة; حسن, ضاحي (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research tries to identify the aesthetic features of the rhetorical composition in the literature of Gibran Khalil Gibran after viewing the concept of rhetoric and aesthetic functions performed in literary texts, and identifying these aesthetics as proven by critics. The study focuses on the aesthetics of comparison and contrast, aesthetics of considering the counteractive, aesthetics of combining, separating and dividing, and aesthetics of verbal improvements, then testing their role in Gibran's poetic and prose texts, focusing on the rhetorical arts that dominate these texts, through selected poetic and prose models of the writer's creativity .